2011
DOI: 10.2134/jeq2010.0412
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Prions in Soil: A Review

Abstract: Prions are the etiological agents of transmissible spongiform encephalopathies (TSEs), a class of fatal neurodegenerative diseases affecting humans and other mammals. The pathogenic prion protein is a misfolded form of the host-encoded prion protein and represents the predominant, if not sole, component of the infectious agent. Environmental routes of TSE transmission are implicated in epizootics of sheep scrapie and chronic wasting disease (CWD) of deer, elk, and moose. Soil represents a plausible environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 159 publications
0
65
0
Order By: Relevance
“…PrP CWD has changed by binding with HA but the exact mechanism of this process is still unclear. 40 In other studies, 44 it was suggested that negativelycharged HA could encapsulate positively-charged proteins and preserve their activity. A more recent study 20 has shown HA-like substances copolymerize with recPrP and irreversibly involve the PrP in their structure creating complexes which decrease recPrP recovery.…”
Section: Soil Organic Mattermentioning
confidence: 98%
See 2 more Smart Citations
“…PrP CWD has changed by binding with HA but the exact mechanism of this process is still unclear. 40 In other studies, 44 it was suggested that negativelycharged HA could encapsulate positively-charged proteins and preserve their activity. A more recent study 20 has shown HA-like substances copolymerize with recPrP and irreversibly involve the PrP in their structure creating complexes which decrease recPrP recovery.…”
Section: Soil Organic Mattermentioning
confidence: 98%
“…Prion-SOM interactions are not well characterized. 40 In studies where the ability of SOM compounds to bind uninfectious recombinantly generated PrP was investigated, the affinity of SOM for recPrP was almost equivalent to that offered by the clay mineral surfaces. [17][18][19][20] In addition, pure HA not only exhibited the strongest affinity for recPrP but also increased (about 10×) the sorption capacity of kaolinite and Mte clays.…”
Section: Soil Organic Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogens are a result of normal, human metabolic wastes as well as additional loading from medical effluents (Arthurson, 2008;Deblonde et al, 2011;Lewis et al, 2002;Mathney, 2011;Reilly, 2001;Straub et al, 1993;USEPA, 2009;Verlicchi et al, 2010). There are fewer than two dozen pathogens (e.g., fecal coliforms, Salmonella, enteric viruses, and parasites) monitored in sewage sludge (Mathney, 2011;NASNRC, 2002;Reilly, 2001;Snyder, 2005;USEPA, , 2002bUSEPA, , 2003, and many dangerous pathogens (e.g., prions) are neither affected by sewage treatment nor detected by standard analytical methods (Gale & Stanield, 2001;NASNRC, 2002;Peterson et al, 2008b;Saunders et al, 2008;Smith et al, 2011;Snyder, 2005).…”
Section: Pathogensmentioning
confidence: 99%
“…[27][28][29][30] However, other soil characteristics, such as natural oxidants like manganese oxides (MnO 2 ), appear to interfere with the conversion of PrP C to PrP Sc . 31 To our knowledge there is no data regarding the concentration of Mn, Cu, Fe and Mg in obex and RLN of white-tailed deer even though these tissues are the preferred sites for diagnostic sampling and testing for CWD, and target sites for PrP Sc accumulation during infection.…”
Section: Introductionmentioning
confidence: 99%